Gay In Will Grayson, Will Grayson Novel By John Green And David Levithan (2010): Queer Theory - AYUNINGTYAS, DESY, Dr. Phil. Dewi Chandraningrum, M. Ed (2017)
This research intends to describe how the character of a gay,and what kind of gay is reflected in Will Grayson, Will Grayson novel by John Green and David Levithan. This reseacrh is a descriptive qualitative research which is done under the framework of Queer Theory. This research takes Will Grayson, Will Grayson novel by John Green and David Levithan as source of data. Some forms of its word, setence, and dialogues are taken as primary data. Based on the analyze, the reseacher obtain some conclussions. This research show that second Will Grayson version David Levithan as a gay who is depression. This research show that the problem faced by major and minor character who is also a gay. It is proven by their life that they have been falling in love with the same gender.